Application of the theory of sovereignty in the Algerian constitutions - Bouguerit, Omar (Journal of Human Sciences, 2020)
The theory of sovereignty is one of the most important theories in the field of constitutional law because of its impact on the legitimacy of authority and its limits. The constitutions of modern countries have taken up this theory, including the Algerian constitutions. There are those who have taken both theories and combined them, including the Algerian constitutional founder, adopting some of the mechanisms of the theory of national sovereignty and the theory of the sovereignty of the people.